2015
DOI: 10.1007/s00117-014-2801-9
|View full text |Cite
|
Sign up to set email alerts
|

Ganglienblockade

Abstract: The CT-guided procedure for neurolysis of the celiac plexus is safe and effective in diminishing pain especially in patients suffering from tumors of the upper abdomen. The procedure can be repeated if the effect is only temporary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…CT-guided CPN for abdominal visceral pain achieve moderate or major short-term pain relief in a majority of cases and the procedure is safe with minimal complications 10 and this is in agreement with our study and also with Krämer et al 11 who concluded that CT-guided procedure for neurolysis of the celiac plexus is safe and effective in diminishing pain especially in patients suffering from tumors of the upper abdomen.…”
Section: Discussionsupporting
confidence: 92%
“…CT-guided CPN for abdominal visceral pain achieve moderate or major short-term pain relief in a majority of cases and the procedure is safe with minimal complications 10 and this is in agreement with our study and also with Krämer et al 11 who concluded that CT-guided procedure for neurolysis of the celiac plexus is safe and effective in diminishing pain especially in patients suffering from tumors of the upper abdomen.…”
Section: Discussionsupporting
confidence: 92%
“…Celiac ganglion and plexus blocks or neurolysis have been used for decades in an attempt to alleviate the pain (Akinci & Akham, 2005; Ascunce et al, 2011; Gerke et al, 2006; Levy, 2009; Loukas et al, 2010; Minaga et al, 2018; Moore & Adler, 2009; Zhang et al, 2006). Percutaneous approaches with fluoroscopy or CT guidance using the vasculature as landmarks and endoscopic techniques passing through the stomach have been used but the results vary greatly (Akinci & Akham, 2005; Fitzgibbon et al, 2001; Kramer et al, 2015; Levy, 2009; Wang et al, 2006). Not only does the posterior percutaneous approach require bilateral puncture of the aorta it risks damage to the spinal cord (Akinci & Akham, 2005; Moore & Adler, 2009).…”
Section: Introductionmentioning
confidence: 99%